Development of a Decision Support System in Ship-To-Ship Lightering. (28th March 2016) - Husjord, Dagfinn
Abstract : This paper focusses on the development of a tool for decision-making, tailored for personnel involved in complex Ship-To-Ship (STS) operations, to enhance the efficiency and safety of these operations. A step-wise approach has been selected. The first step includes specification, development and testing of the tool in a simulated work environment using full-mission simulators. In the second step the findings from application of the tool in the simulated work environment will be used to develop a prototype which will be tested during real life STS operations. This paper describes work done in the first of these two steps. During four iterations, a Graphical User Interface (GUI) has been made following Interaction Design (IxD) principles. The designs have been iteratively developed and tested by experienced ship's officers in a ship-handling simulator to clarify key information to enhance their Situation Awareness (SA) and decision-making process. In order to find indicators for performance, an initial performance test was carried out in a ship-handling simulator. The test indicates that a logic based Decision-Support System (DSS) can improve existing simulator-based training activities in STS operations.